Sociodemographic factors in the risk of preterm birth in pregnant women at the Sergio Bernales hospital in the period 2019-2020 - Chavez-Mauricio, Ronni Delinger (2023)
Objective: To determine the relationship of sociodemographic factors and the risk of premature delivery in pregnant women of the Sergio Bernales hospital in the period of 2019-2020. Materials and methods: Observational, analytical, retrospective, and case-control study sought to quantify the relationship between sociodemographic factors and the risk of preterm birth. A review of medical records corresponding to the Gynecology-Obstetrics service of the Sergio Bernales Hospital was used. The data obtained were studied using the SPSS program and an association was sought using bivariate analysis. Results: From the study of 300 pregnant women, the analysis was carried out for 100 pregnant women with a diagnosis of preterm birth who constituted the cases and 200 pregnant women as the control group. In the bivariate analysis, it was found that preterm birth was associated with rural or foreign origin (p<0.01); OR: 3.51, 95% CI = [2.03-6.06], extream ages (p<0.01); OR: 2.72 with a 95% CI = [1.53-4.85], and unaffiliated to SIS (p<0.03); OR: 2.59 with a 95% CI = [1.07-6.21]. Conclusions: Rural or foreign origin, extream ages and unaffiliated to SIS are factors associated with the risk of preterm birth.